Kikuchi-Fujimoto disease following SARS-CoV-2 vaccination. Issue 11 (22nd November 2022) - Ikeda, Kohsuke; Kakehi, Eiichi; Adachi, Seiji; Kotani, Kazuhiko
Abstract : A previously healthy Japanese woman in her 20s was admitted to our hospital with a 2-week history of fever (39.0°C) and a 1-week history of painful cervical lymphadenopathy. The day before fever onset, she had received her first Pfizer-BioNTech SARS-CoV-2 vaccine in her left arm. She had previously been treated with empirical antibiotics with no improvement. Physical examination revealed painful lymphadenopathy in both posterior cervical regions. CT showed symmetrical lymphadenopathies in the neck, supraclavicular, axillary and inguinal regions as well as hepatosplenomegaly. We suspected lymphoma and performed a lymph node biopsy in the right inguinal region, which revealed necrotising histiocytic lymphadenitis. The patient was, therefore, diagnosed with Kikuchi-Fujimoto disease (KFD). She improved after the corticosteroid therapy. This report highlights the importance of including KFD as a differential diagnosis of lymphadenopathy after SARS-CoV-2 vaccination. Additionally, lymph node biopsy is helpful for diagnosing KFD because it rules out other entities.